Linoleic acid-derived 13-hydroxyoctadecadienoic acid is absorbed and incorporated into rat tissues - Zhang, Zhichao (Biochim Biophys Acta Mol Cell Biol Lipids, 2020)
Linoleic acid (LNA)-derived 13-hydroxyoctadecadienoic acid (13-HODE) is a bioactive lipid mediator that regulates multiple signaling processes in vivo. 13-HODE is also produced when LNA is oxidized during food processing. However, the absorption and incorporation kinetics of dietary 13-HODE into tissues is not known. The present study measured unesterified d4–13-HODE plasma bioavailability and incorporation of into rat liver, visceral adipose, heart and brain following gavage or intravenous (IV) injection (n=3 per group). Mass spectrometry analysis revealed that d4–13-HODE was absorbed within 20 minute of gavage, and continued to incorporate into plasma esterified lipid fractions throughout the 90 minute monitoring period. Following IV injection, unesterified d4–13-HODE was rapidly eliminated from plasma with a half-life of 1 minutes, whereas the gavaged tracer incorporated into esterified lipid pools and had a half-life of 71 min. Analysis of tracer incorporation kinetics into rat tissues following IV injection or gavage revealed that the esterified tracer preferentially incorporated into liver, adipose and heart compared to unesterified d4–13-HODE. No tracer was detected in the brain. This study provides new evidence that dietary 13-HODE is absorbed, and incorporated into peripheral tissues from esterified plasma pools. Understanding the chronic effects of dietary 13-HODE exposure on peripheral tissue physiology and metabolism merits future investigation.